Efeitos do gradiente de elevação em assembléias de aranhas edáficas em um brejo de altitude cearense - Azevedo, Raul (2023)
The present work lists the results of a continuous research of medium duration (13 monthsof research) carried out in a Brejo de Altitude in the state of Ceará. The effects of theelevation gradient (from 373 to 1114m) on diversity of spiders were studied. Weinvestigated over 13 months how the elevation gradient variation influenced the variationin species richness of edaphic spiders, as well as the occurrence of the Rapoport Effect;how the elevation gradient increases rainfall and how this increase in rainfall increasesthe abundance of collected macrofauna and edaphic spiders over thirteen months ofsampling. The results obtained allowed observing the initial decrease and subsequentincrease in species richness as a function of the increase in the elevation gradient, thuscontradicting the existing climate models that correlate species richness and elevationgradients. The data also demonstrated the occurrence of the Rapoport Effect. Theobtained data also demonstrate that the elevation gradient modifies how the edaphicspiders respond to rainfall variation and macrofauna variation.